THE IMPORTANCE OF PHYSICAL EDUCATION AND SPORTS IN THE EDUCATION OF THE YOUNG GENERATION - Dekhkonova Makhmuda Ortigovna (Journals Park Publishing, 2022)
"Sport is a guarantee of health", therefore, we should all constantly engage in some type of sport, consider it an integral part of our lives. The article discusses these things.
Keywords: Sport, I.A. Karimov, Bukhara, Samarkand, mature generation, youth, football.